Proceedings of the 2008 compFrame/HPC-GECO Workshop on Component Based High Performance 2008
DOI: 10.1145/1456190.1456199
|View full text |Cite
|
Sign up to set email alerts
|

A component infrastructure for performance and power modeling of parallel scientific applications

Abstract: Characterizing the performance of scientific applications is essential for effective code optimization, both by compilers and by high-level adaptive numerical algorithms. While maximizing power efficiency is becoming increasingly important in current high-performance architectures, there is little or no hardware or software support for detailed power measurements. Hardware counter-based power models are a promising method for guiding software-based techniques for reducing power. We present a component-based in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This benchmark is denoted as idl. 2. linpack: This pre-compiled linear algebra code from Intel contains the optimized LINPACK [31] benchmark 5 . Internally using MKL libraries, it performs FPU/ALU instructions with the purpose of utilizing the CPU.…”
Section: Target Platform and Benchmark Suitementioning
confidence: 99%
See 2 more Smart Citations
“…This benchmark is denoted as idl. 2. linpack: This pre-compiled linear algebra code from Intel contains the optimized LINPACK [31] benchmark 5 . Internally using MKL libraries, it performs FPU/ALU instructions with the purpose of utilizing the CPU.…”
Section: Target Platform and Benchmark Suitementioning
confidence: 99%
“…However, acquisition costs and deployment of power measurement devices can be, due to the nature of the platforms and number of nodes, infeasible. Recent research has significantly demonstrated that a promising alternative in order to mitigate this issue is the design of power models [3,4,5]. Taking into account that most of the current processors feature a large set of hardware counters, temperature sensors, and resource usage statistics provided by the operating system, one could cleverly use this information to predict power drawn by individual components and system power consumption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression-based power modeling approach used in TProf to account energy between concurrently executing tasks follows a long line of earlier work that derives power models using input from hardware performance counters [4,8,9,10,23,36]. Prior work establishes power models composed of linear or piecewise polynomial functions of sampled hardware event rates, using events that correlate strongly with power consumption.…”
Section: Related Workmentioning
confidence: 99%
“…In the database component, the user can set parameters such as the name of the configuration and the name of the loader utility in cases where an external, non component tool is exploited to import the data into a database. Other implementations of the database interface do not rely on external tool support for importing data into the database, for example the database components available as part of CQoS infrastructure [6]. This design allows the easy addition of new components to support multiple data formats, transfer protocols, and database interfaces.…”
Section: Importing Performance Datamentioning
confidence: 99%